2003
DOI: 10.1253/circj.67.781
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol Improves Cardiac Dysfunction After Ischemia-Reperfusion via Reduction of Oxidative Stress in Isolated Perfused Rat Hearts

Abstract: It has been reported that the xanthine oxidase inhibitor, allopurinol, has a protective effect on ischemia - reperfusion injury, but the precise mechanism of its action is still unclear. Therefore, in the present study the mechanisms of the myocardial protection of allopurinol were evaluated in isolated perfused rat hearts. Allopurinol significantly inhibited myocardial xanthine oxidase activity, and improved left ventricular dysfunction after ischemia - reperfusion. In addition, the lactate dehydrogenase cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 38 publications
4
65
0
2
Order By: Relevance
“…1 Oxidative stress induced by superoxide generated via the xanthine oxidase system and infiltrating inflammatory cells is the major proposed mechanism of MIR progression. [2][3][4][5] We have reported that reactive oxygen species (ROS) influence the opening of the mitochondrial permeability transition pore in myocardial cells, which led to progression of myocardial infarction (MI) in a rat MIR model. 6 Moreover, total nitric oxide (NO) synthesis in the reperfused heart was increased in previous investigations.…”
mentioning
confidence: 99%
“…1 Oxidative stress induced by superoxide generated via the xanthine oxidase system and infiltrating inflammatory cells is the major proposed mechanism of MIR progression. [2][3][4][5] We have reported that reactive oxygen species (ROS) influence the opening of the mitochondrial permeability transition pore in myocardial cells, which led to progression of myocardial infarction (MI) in a rat MIR model. 6 Moreover, total nitric oxide (NO) synthesis in the reperfused heart was increased in previous investigations.…”
mentioning
confidence: 99%
“…However, previous studies have shown that antioxidant drugs improve post-ischemic cardiac dysfunction in isolated hearts. 22,23 Therefore, because nicorandil has been reported to have many beneficial effects, such as opening the mitochondrial KATP channels, 4,5 inhibiting apoptosis, 24 inhibiting platelet aggregation, 25 direct preservation of mitochondrial function, 26 and coronary capillary architecture and volume, 27 besides free radical scavenging effects, it is still difficult to say whether the decrease in 2,3-DHBA concentration is the main cause of the attenuation of ischemia -reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Next, they were subjected to a 30-min no flow global ischemia, followed by 60 min of reperfusion. 16 The successful induction of ischemia was determined by ST elevation on the electrocardiogram. Heart rate and perfusion pressure were constantly monitored.…”
Section: Isolation and Preparation Of The Heartmentioning
confidence: 99%